Comprehensive examination of support needs and mental well-being: a mixed-method study of the Austrian general population in times of crisis - Dinhof, Carina; Humer, Elke; Haider, Katja; Rabenstein, Rafael; Jesser, Andrea; Pieh, Christoph; Probst, Thomas; Gächter, Afsaneh (Frontiers in Public Health, 2024)
Introduction In the recent years, the Austrian general population has faced a confluence of multiple crises. This study investigates the support wishes and mental health parameters of the Austrian general population aiming to comprehending the unmet needs and providing guidance for future psychosocial interventions and research endeavors. Methods 1,031 participants attended the online survey and one third (n = 332) wished for further support to improve mental well-being in April 2022. A total of 280 participants accompanied their support wish with written accounts. Participants’ mental health status was evaluated using the PHQ-9 (depression), GAD-7 (anxiety), ISI (insomnia), PSS-10 (perceived stress), CAGE (alcohol abuse), WHO-5 (well-being), and the SCOFF (eating disorder) questionnaires. Data analysis employed a mixed-methods approach. Results The preeminent support wish identified was the need for professional mental support (29.3%), followed by communication (21.6%), other professional support except mental and medical support (13.9%). In line with these findings, participants expressing a support wish experienced increased mental health distress across all assessed parameters. Conclusion The findings indicate the presence of a vulnerable population within the Austrian general population, which may benefit from targeted support interventions. Consequently, this study contributes to the identification of unmet support needs among the Austrian populace during times of crisis, facilitating the development and enhancement of precisely tailored intervention strategies.